REPRESENTATIONS OF GENDER SOLIDARITY ON FEMINISM: ANALYSIS OF THE INFLUENCE OF MALE FIGURES IN THE MOVIE KARTINI (2017) - Agustin, Azahra Hirosi Nur (Serat: Journal of Literary & Cultural Studies, 2024)
The movie industry has undergone a significant evolution. Initially regarded as a mere entertainment medium, it has now evolved into a highly influential medium for conveying cultural values that reflect the realities of society, as one of the heroic-themed films by Hanung Bramantyo, entitled Kartini. Released in 2017, Kartini recounts the struggles of Raden Ajeng (R.A.) Kartini, a pioneering figure in the Indonesian feminist movement, who faced the constraints of patriarchy by Javanese ancient tradition. In the context of feminism, there is a common misconception about feminism that it is perceived as an anti-male movement. Kartini is interesting to discuss because it presents the complexity of R.A. Kartini's relationship with the male figures around her in a patriarchal and feudal environment of ancient Javanese traditions. This research employs a descriptive-qualitative analysis approach to identify how the male figures in the movie contribute to the narrative of gender equality. Furthermore, it employs Bell Hooks's feminism theory to demonstrate that the concept of feminism is not exclusively by and for women. The analysis findings indicate that the construction of the relationship between R.A. Kartini and several male figures around her contributed to the presence of her progressive thinking. The findings concluded that male figures' contribution to R.A. Kartini's progressive thinking in the fight for gender equality can be described as a form of gender solidarity. The study argues that the findings have significant implications for enhancing our comprehension of the importance of gender solidarity and support for feminism in pursuing gender equality.